TEORI AL-MUNASABAH (FUNGSI KORELASI AYAT DAN MODEL AL-MUNASABAH DALAM PENAFSIRAN AYAT KEWARISAN (Pascasarjana Institut Agama Islam Almuslim Aceh, 2024)
The research aims to describe the existence of correlation namely Munasabah between An-Nisa‘; 11 and An-Nisa‘; 34 in title, object, revelation by determining the proportional heritage which then converts to the part of heritage when the heirs grow up particularly when they are married. The research is a qualitative research using descriptive analyze. The collection data uses literature study of interpretation, The research of result indicates Munasabah as Imam Suyuthi stated that Munasabah could function as a tool of affirmation or it strengthens the correlation between two verses. Both of verses are mutually affirmative and each stresses on the correlation. An-Nisa‘; 34 renders two significant analyzing, namely ta’lil wahbi and ta’lil kasbi. The former is called the reasoning for a gift, which stresses on superiority gift given to the men naturally such us stronger body and gender. In this case the physical ability is apparently stronger than the natural gift given to the women. The later is reasoning to give, which means that Allah has been bestowing roles and duties to the men as caretaker of home, giving life to his family, wife and his sons/daughters. These two requirements must run in balance that the man must have the physical and spirit ability which then he would be capable of being Qawwam and home caretaker as well as a leader in his family.